Optimization of Flour Smoke Making Through Microencapsulated Technology as Food Natural Preservatives - Abrina Anggraini, Sinar Perbawani; Suryanti, Fenni (Jurnal IPTEK, 2020)
There should be a safe natural preservatives consumed to increase the shelf life of food products. Liquid smoke is a natural food preservative. Liquid smoke if left longer in storage will reduce the saving power of food products. There is a need to develop technology by changing liquid smoke into flour through microencapsulation technology so that it will improve the save power of food products. This research aims to determine long storage time and the optimal drying temperature in the manufacture of microparticle solutions to the quality of food products. In this research the process of pyrolysis and purification of liquid smoke from coconut shell by using pyrolysis, distillation and filtration processes using active zeolite and activated carbon. Then make solution encapsulation, drying, forming microparticles with destruction and sieve, after that applied to food products. Results of the research on the manufacture of optimum smoked flour in the treatment of drying temperature of 140 oC and maximum storage time 3 days with a pH value of 5, water content 28.470% and 3.120% protein content